The Principle of Legal Certainty in the Implementation of Projects Funded by the State Budget (APBN): Reformulating an Adaptive Contract Model and Digital Governance for Public Procurement in Indonesia - Mochamad Ichsan; Sami'an Sami'an; Sarwono Hardjomuljadi (Interdisciplinary Social Studies, 2025)
Implementation of government projects funded by the State Revenue and Expenditure Budget (APBN) still often faces legal uncertainty problems, particularly in the implementation of public construction contracts affected by price fluctuations, complex project risks, and suboptimal dispute resolution mechanisms. The principle of legal certainty—an essential foundation of public administration—has not been fully realized consistently in government goods and services procurement practices. This research uses a normative juridical method with a statutory and conceptual approach, aiming to formulate an adaptive contract model and a digital law governance framework relevant to the dynamics of state construction projects. The findings show the need to reformulate a more robust contract model that is responsive to changing conditions through the implementation of price adjustment clauses, proportional risk distribution, and the use of dispute boards as preventive dispute-resolution instruments. Moreover, the integration of digital systems such as SPSE (Electronic Procurement System), e-monitoring, and smart legal dashboards plays a significant role in strengthening data-based legal certainty and enhancing transparency in the procurement process. Based on these findings, the research recommends updating regulations and designing more adaptive construction contracts to support accountability, efficiency, and strengthen public trust in the implementation of national strategic projects.